2008
DOI: 10.1016/j.mcn.2007.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell factor and mesenchymal and neural stem cell transplantation in a rat model of Huntington's disease

Abstract: Neural and mesenchymal stem cells have been proposed as alternative sources of cells for transplantation into the brain in neurodegenerative disorders. However, the endogenous factors controlling their engraftment within the injured parenchyma remain ill-defined. Here, we demonstrate significant engraftment of undifferentiated exogenous mesenchymal or neural stem cells throughout the lesioned area in a rat model for Huntington's disease, as late as 8 weeks post-transplantation. We show that stem cell factor (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 69 publications
2
46
0
1
Order By: Relevance
“…Dysfunctional or morphologically altered PCs, but in normal or nearly normal number, did not generate a strong enough signal to attract NPCs. The nature of the attractive signal is not determined, but we know that in other systems (basal ganglia, brain hemispheres), growth factors (Ghosh and Greenberg, 1995;Kuhn et al, 1997;Zhang et al, 2003) and chemokines (Imitola et al, 2004;Bantubungi et al, 2008) (S. Chintawar, A. Ravella, M. Pandolfo unpublished results) generated at the site of injury can act as a migratory and/or a prodifferentiating factor. Grafted NPCs that remained near the injection sites in the white matter generally adopted an astroglial phenotype and were GFAP pos .…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctional or morphologically altered PCs, but in normal or nearly normal number, did not generate a strong enough signal to attract NPCs. The nature of the attractive signal is not determined, but we know that in other systems (basal ganglia, brain hemispheres), growth factors (Ghosh and Greenberg, 1995;Kuhn et al, 1997;Zhang et al, 2003) and chemokines (Imitola et al, 2004;Bantubungi et al, 2008) (S. Chintawar, A. Ravella, M. Pandolfo unpublished results) generated at the site of injury can act as a migratory and/or a prodifferentiating factor. Grafted NPCs that remained near the injection sites in the white matter generally adopted an astroglial phenotype and were GFAP pos .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was suggested that MSCs, by producing growth factors, allowed surviving cells within the caudate nucleus to function more efficiently and to facilitate other compensatory responses (Dunbar et al, 2006). In this regard, another study demonstrated the importance of factors such as stem cell factor (SCF), produced in situ in the lesioned striatum, to promote the migration and engraftment of MSCs via SCF receptor c-kit (Bantubungi et al, 2008). In the context of PD, several teams, including ours, reported the neuronal differentiation of human MSCs toward a dopaminergic phenotype in vitro, indicating that these cells may constitute an alternative dopamine secreting source of cells (Trzaska & Rameshwar, 2011;Barzilay et al, 2008;Trzaska et al, 2007;).…”
Section: Adult Cell Therapymentioning
confidence: 82%
“…In theory, this injection should be performed as close as possible to the target organ. In the past, intrarenal injection was considered the optimal route for cell transplantation to the kidney since it is the closest to the target organ [11]. However, cells transplanted by this route usually failed to ameliorate the disease pathology in the kidney as the limited diffusion of nutrients and oxygen [12] was insufficient for successful engraftment of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the cells are preferentially administered into the aorta [3,10] or even the carotid artery [11], as the first pass through the lungs prevents many cells from reaching the kidney immediately after the injection. Nevertheless, as stem cells are known to home to sites of inflammation [13], a systemic injection remains a defendable strategy.…”
Section: Discussionmentioning
confidence: 99%